The effectiveness oxytocin massage combination moringa leaves and soy milk on breastmilk production postpartum mothers - Umaroh, Umaroh; Hardjanti, Triana Sri; Rahfiludin, Mohammad Zen (International Journal of Public Health Science (IJPHS), 2024)
Breastfeeding is very influential on infants’ and child’s growth. Survey result in 2018 mentioning the coverage of exclusive breastfeeding is 68.74% in Indonesia and 64.19% in Central Java. Some factors caused breastfeeding obstructions are breast milk didn’t ooze and small quantity of the ooze. Breast milk obstruction caused due lack of oxytocin and prolactin hormone stimulation. This can be cured by giving moringa leaves and oxytocin massage. The study's goal is to examine breast milk production after a combination oxytocin massage with moringa leaves and soy milk. The research design is quasi-experimental with a post-test only control group, and the data analysis design is an independent T-test. Population of this study is postpartum mothers in Central Java. With 83 total samples in Salatiga, Semarang, Grobogan, Rembang, Blora, Kendal and Demak. The group combined with moringa leaves, has 1,183.24 grams difference weight before and after treatment, estimated 185.21 ml volume of breast milk. The group combined with soy milk, has 1,088.04 grams difference weight before and after treatment, with 170.31 ml estimated of breast milk volume. The difference baby's weight from two combination groups was 95.2 grams with a p-value of 0.108. Conclusion of the study is the difference is not significant. The weight gain of infants in the oxytocin massage combination with moringa leaves group was higher than soy milk combination. Recommendation of moringa leaves can be offer for postpartum mother to increase the ooze of breast milk production.